Experiences from the urban planning process of a solar neighbourhood in Malmö, Sweden. Issue 1 (1st January 2018) - Kanters, Jouri; Wall, Maria
Abstract: Many cities have set ambitious goals regarding the production of renewables within cities using advanced energy planning. The crux of those ambitious plans and goals is to put them into action using different legislative instruments, like a zoning plan. In this article, the experiences of an action research project with the aim to support local urban planners developing a zoning plan that creates favourable conditions for solar energy in Malmö, Sweden, are described. The Swedish planning process, national legal framework and financial conditions for PV systems are described first. Then, different scenarios for optimising the zoning plan were studied, using mainly the economic performance as a key indicator. The results showed that the detailed development plan does create both barriers and drivers for the implementation of PV systems in new buildings. At the same time, it also became clear that the legal and financial framework are equally decisive. By describing the lesson learnt, the method can be applied to other (inter)national contexts.